DEBATING THE DOCUMENTS OF THE HOLY AND GREAT SYNOD OF CRETE – A CANONICAL AND DISCIPLINARY APPROACH. CASE STUDY: THE ARCHBISHOPRIC OF IAŞI - ROMAN, Emilian-Iustinian (Studia Universitatis Babeș-Bolyai Theologia Orthodoxa, 2017)
The discussion of the documents of the Holy and Great Synod of Crete has resulted in numerous clashes in the dioceses of the Romanian Patriarchate. In this context, our study seeks to analyse various forms of canonical disobedience and highlight the principle of synodality, one of the fundamental canonical principles of organizing the Orthodox Church, according to which the leadership of the Church is exercised collectively, not individually. Furthermore, canonical obedience, as an expression of the hierarchical principle, means the subordination of the inferior ranks to the higher ones, of the faithful to the hierarchy, of the hierarchs to the synods, etc.